An analysis of the public reporting of organisational resilience found within the integrated reports of a large state-owned enterprise - Fleming, Linda (Rhodes University, Faculty of Commerce, Rhodes Business School, 2020)
This research explored whether there is any evidence of reporting of organisational resilience within the integrated reports of a large state-owned enterprise. The organisation chosen for the research was Eskom. The integrated annual reports of Eskom for 2016, 2017 and 2018 were examined. Direct and indirect evidence of organisational resilience was sought within the organisations integrated reports. The direct reporting of organisational resilience was located by using a PDF word search. A thematic content analysis was used to perform the search for indirect reporting of organisational resilience. Three main themes to represent organisational resilience that were identified beforehand were used to identify the indirect reporting of organisational resilience. Namely, transformability, adaptability and persistence. Sub themes of general and specified resilience were also identified during the research process. The literature review discusses the themes in detail, and also introduces communication and integrated reporting. Evidence of both direct and indirect organisational resilience was identified in all three years studied. Evidence of all the main themes and sub themes was found within the indirect reporting of organisational resilience. The main limitation of the study is that although evidence of reporting of organisational resilience was found, this evidence does not provide any indications of the level of organisational resilience within Eskom. A number of recommendations to Eskom management are made at the end of the research. What is interesting is that integrated reports are not designed to report on organisational resilience. However, the research showed clear evidence of reporting of organisational resilience within all three years researched. Potentially indicating that the integrated annual reports are a useful method of sharing information regarding organisational resilience with stakeholders. An additional benefit is that communication with stakeholders is simultaneously contributing to the enhancement of the organisations resilience.
Keywords: Eskom (Firm); Organizational resilience; Eskom (Firm) -- Management